REPRESENTAÇÕES SOCIAIS DE HOMENS GAYS SOBRE HOMENSGAYS COM DEFICIÊNCIA VISUAL - Geíza Ferreira dos Santos (2023)
The way in which the individual with a disability is perceived is linked to values in different historical and cultural moments. The Declaration of the Rights of Persons with Disabilities of the United Nations (UN) brought to light the rights of this public, reinforcing the global need to guarantee them in all signatory countries. These people, even endowed with rights that ensure their full integration into society, find it difficult to exercise their sexuality. Because they are not suited to a socially imposed standard, gay men with visual impairments may still suffer prejudice related to their own group, in this case, gay men without visual impairments. Thus, this research aims to identify and analyze the Social Representations (SR) of gay men about gay men with visual impairment. The research was based on the perspective of the Theory of Social Representations (TRS) and, more specifically on the Theory of the Central Nucleus of Jean-Claude Abric. The study included 105 gay men (Cis or Trans), residing in the state of Mato Grosso do Sul. Of the respondents, 86 were elective and signed the acceptance term, in addition to responding to a virtual form, aiming to draw a sociodemographic profile. Substitution techniques were used to analyze the mute zone and the Free Word Association Technique (TALP), from the evocators: gay man, visual impairment and gay man with visual impairment. Data were analyzed with the help of the Iramuteq software, through prototypical and similarity analysis. Thus, for the inducing term “gay man”, the following words were evoked in a normal situation: “Freedom”, more frequently representing the hard core of the representations and “rainbow”, less frequently. In a situation of substitution, the words: “sex”, in greater frequency and “gym” with less frequency, appeared. For the inducing term “visual impairment”, “accessibility” and “guide dog” emerged less frequently. In the silent zone, “Difficulty” appeared as the central nucleus and “Support” with little frequency. For the inducing term “gay man with visual impairment”, in a normal situation words like “Prejudice” emerged as the hard core and “Disability” in less frequency. In the mute zone, the words “prejudice” appear as the central core and “empathy” in the contrast zone. In summary, the words that emerged with the inducing terms in a normal situation and in a substitution situation reveal that the people investigated have an image about the visually impaired public based on the context of respect for rights, present in the words “accessibility” and “dog- guide". However, the word “Prejudice” emerged in a normal situation and in a substitution situation as centrality when referring to the inducing term “gay man with visual impairment”, in contrast to the words related to the inducing term “gay man” which were “freedom”. and “sex” in normal situation and in substitution respectively. The results of this research suggest a lack of understanding about the potential of gay men with visual impairment on the part of the researched gay men, since terms that border on capacitism emerged, showing that these are elective for a relationship by the researched public only as “curiosity” and “fetish”, denoting a marginalized perspective, revealing a silent violence, in addition to prejudice and discrimination within the LGBTQIAP+ acronym itself. Keywords: Visual Impairment; Gay Men; Social Representations.